2015
DOI: 10.1373/clinchem.2014.235457
|View full text |Cite
|
Sign up to set email alerts
|

Brain Tumor Mutations Detected in Cerebral Spinal Fluid

Abstract: BACKGROUND Detecting tumor-derived cell-free DNA (cfDNA) in the blood of brain tumor patients is challenging, presumably owing to the blood–brain barrier. Cerebral spinal fluid (CSF) may serve as an alternative “liquid biopsy” of brain tumors by enabling measurement of circulating DNA within CSF to characterize tumor-specific mutations. Many aspects about the characteristics and detectability of tumor mutations in CSF remain undetermined. METHODS We used digital PCR and targeted amplicon sequencing to quanti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
203
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 246 publications
(208 citation statements)
references
References 27 publications
4
203
0
1
Order By: Relevance
“…Therefore, based on the study above and our current study, the blood-brain barrier does not preclude primary brain tumors from shedding ctDNA into the circulation (31). For patients with primary brain cancers, cerebrospinal fluid may also serve as an alternative "liquid biopsy" (32).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, based on the study above and our current study, the blood-brain barrier does not preclude primary brain tumors from shedding ctDNA into the circulation (31). For patients with primary brain cancers, cerebrospinal fluid may also serve as an alternative "liquid biopsy" (32).…”
Section: Discussionmentioning
confidence: 99%
“…Brain tumor mutations can now be detected in the cell-free DNA of cerebrospinal fluid. 64,91 In a recent proof-of-principle study, elevated cell-free RNA transcripts of APP and PSD3 were identified in the serum of patients diagnosed with Alzheimer's disease, while transcripts associated with neural development were detectable in peripheral blood of women during pregnancy.…”
Section: Work In Progressmentioning
confidence: 99%
“…However, due to blood-brain barrier (BBB), patients with brain tumors do not present with or present with only low amounts of ctDNA in plasma (17). Recently, a few studies have demonstrated that tumor mutations are detectable in the CSF of patients with various primary and metastatic brain tumors, and ctDNA in CSF recapitulates the genomic landscape of brain tumors better than plasma (18)(19)(20). Therefore, CSF may serve as liquid biopsy to monitor brain tumor evolution.…”
Section: Introductionmentioning
confidence: 99%